2010
DOI: 10.1111/j.1365-2036.2009.04203.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic profile of immediate‐release omeprazole in patients with gastro‐oesophageal reflux associated with gastroparesis

Abstract: SUMMARY BackgroundImmediate-release omeprazole has a more rapid absorption compared with delayed-release omeprazole in asymptomatic volunteers. However, effects of delayed gastric emptying on omeprazole absorption remain unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Omeprazole mean (SD) plasma concentrations at 1.5 hours after the fourth and fifth doses were similar to the previously published omeprazole 40 mg once-daily PK data. 33 Pharmacodynamics Mean PT-time profiles of rivaroxaban were similar between both treatments; PT was increased after rivaroxaban administration for both treatments, with the maximum increase in PT observed approximately 4 hours after rivaroxaban administration. For both treatments, PT subsequently decreased gradually and values returned to near baseline by the end of the 72-hour sampling period (Fig.…”
Section: Pharmacokineticsmentioning
confidence: 94%
“…Omeprazole mean (SD) plasma concentrations at 1.5 hours after the fourth and fifth doses were similar to the previously published omeprazole 40 mg once-daily PK data. 33 Pharmacodynamics Mean PT-time profiles of rivaroxaban were similar between both treatments; PT was increased after rivaroxaban administration for both treatments, with the maximum increase in PT observed approximately 4 hours after rivaroxaban administration. For both treatments, PT subsequently decreased gradually and values returned to near baseline by the end of the 72-hour sampling period (Fig.…”
Section: Pharmacokineticsmentioning
confidence: 94%
“…The study in patients with GERD reported that the mean T max was 32 min for IR-O and 97 min for DR-O. The C max was 21 % higher for IR-O than DR-O, but the AUC was similar [ 24 ] . These results were similar to the fi ndings in our study.…”
mentioning
confidence: 95%
“…14 Given such characteristics of AD-206, it can be an alternative to conventional enteric-coated PPIs when rapid absorption or immediate management of symptoms for GERD is needed. 30,31 The systemic exposure of esomeprazole for AD-206 was similar to that of the conventional esomeprazole and satisfied the predetermined equivalent criteria after a multiple-dose for both doses. However, the systemic exposure of esomeprazole in AD-206 was lower than that of the conventional esomeprazole after a single-dose for both doses.…”
Section: Discussionmentioning
confidence: 91%
“… 14 Given such characteristics of AD-206, it can be an alternative to conventional enteric-coated PPIs when rapid absorption or immediate management of symptoms for GERD is needed. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%